Effect of porous coating on two-phase pressure drop of water during up-flow boiling in tubes - Yidiz, Sebiha (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper focuses on the effects of porous coating on two-phase flow pressure drop during up-flow boiling of water in vertical tubes. The experiments were carried out under subcooled fluid-inlet conditions (5-73 K) for different mass fluxes (200-400 kg/m(2) S) and pressures (0.11-0.69 MPa). The measured pressure drops were compared first with each other, and then with correlations from literature. It was found that the best agreement between predicted and measured values is obtained by the method of Thom [3] for a smooth tube and by Muller-Steinhagen and Heck's method [4] for a porous coated tube respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: pressure drop; two-phase up-flow; smooth tube; porous coated tube; water; Thermodynamics; Mechanics